ALTERNATIF STRATEGI KELOMPOK PENGOLAH PEMASAR FAMILY DI KABUPATEN PONTIANAK - E.01108086, Mukhlis (FISIP Universitas Tanjungpura, 2013)
he title of this article is the Alternative Strategies Group Processor Family Marketers inPontianak regency.The purpose of writing this article is to look at the internal and external factorsto get the right strategy in order to increase income developing members through the group.Thisresearch is a qualitative. With all the potential and advantages of its development until now has notundergone significant changes.The results of data analysis showed that the group has a weakhuman resources.Keywords:Internal Factors, External factors, SWOT Analysis and Alternative Strategies.